Mac OS X Hacks - Dornfest, Rael (O'Reilly, 2011)
Mac OS X Hacks reflects the real-world know how and experience of those well steeped in Unix history and expertise, sharing their no-nonsense, sometimes quick-and-dirty solutions to administering and taking full advantage of everything a Unix desktop has to offer: Web, Mail, and FTP serving, security services, SSH, Perl and shell scripting, compiling, configuring, scheduling, networking, and hacking. Add to that the experience of die-hard Macintosh users, customizing and modifying their hardware and software to meet their needs: System Preferences, GUI mods and tweaks, hardware tips, vital shareware and freeware, AppleScript, AppleTalk and equivalents, keyboard modifiers, and general Macintosh-style tomfoolery.